2013
DOI: 10.1063/1.4794918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of size polydispersity on the crystal-fluid and crystal-glass transition in hard-core repulsive Yukawa systems

Abstract: We investigated the effect of size polydispersity on the crystal-fluid transition in hard-core repulsive Yukawa systems by means of Monte Carlo simulations for several state points in the Yukawa parameter space. Size polydispersity was introduced in the system only with respect to the hard particle cores; particles with different diameters had the same surface potential ψ 0 , but the charge per particle was not varied with packing fraction or distance. We observed a shift to higher packing fraction of the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 47 publications
0
35
1
Order By: Relevance
“…For hard-sphere colloids fractionation has been predicted beyond a terminal polydispersity of about 6% [49][50][51][52][53]. For medium-range Yukawa interactions (where κa is between 2.5 and 10), recent simulations [54] have suggested that a size polydispersity of 10%-15%, comparable to ours, is required to hinder crystallization, and thus to potentially trigger fractionation.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…For hard-sphere colloids fractionation has been predicted beyond a terminal polydispersity of about 6% [49][50][51][52][53]. For medium-range Yukawa interactions (where κa is between 2.5 and 10), recent simulations [54] have suggested that a size polydispersity of 10%-15%, comparable to ours, is required to hinder crystallization, and thus to potentially trigger fractionation.…”
mentioning
confidence: 80%
“…The behavior of such polydisperse nanometric dispersions points to directions that have not been explored thus far, despite theoretical predictions [49,[51][52][53][54]60]. We demonstrate here fractionated crystallization, with the coexistence of at least three very different phases (liquid, bcc, and Laves), and the formation of complex crystals that efficiently utilize the full size distribution.…”
mentioning
confidence: 83%
“…In hard-sphere and repulsive colloidal systems, it has been shown that the polydispersity of colloidal particles has a signicant consequence in inhibiting the formation of long-range ordered structures. 15,16 Nevertheless, the polydispersity of colloidal particles has not been taken into account to understand the mechanism of gelation in colloids with competing interactions. Therefore, it is of great interest to understand the role of polydispersity in SALR colloids in the formation of gel states.…”
Section: Introductionmentioning
confidence: 99%
“…For particles with different sizes, the surface potential is assumed to be a constant and A ij is then adjusted accordingly as reported in ref. 16. In simulations, the time is measured in the units of ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi ms max 2 =3 p and the time step is dt ¼ 0.002.The pair interaction is cut off at 8s max .…”
mentioning
confidence: 99%
“…One of the main complications of these systems is that their multi-component character enables coexistence of arbitrarily many fluid or solid phases each accommodating a specific subpopulation of the overall distribution. A prominent example are dense fluids of polydisperse spherical particles where the presence of a range of different sizes may lead to a suppression of crystallization [42,43] in favour of various amorphous states whose nature has been the subject of recent simulation studies [44][45][46]. Alternatively, size polydisperse sphere fluids may develop a coexistence of a number of different solid phases following a pathway referred to as fractionated crystallization [47].…”
Section: Introductionmentioning
confidence: 99%